Anatomical and Morphometric Study of Small and Large Intestine of Bali Cattle - Heryani, Luh Gde Surya; Susari, Ni Nyoman Werdi; Nareswari, Luh Putu Syamadina Pramesya (Journal of Veterinary and Animal Sciences, 2020)
Information on the anatomical and morphometric structure of the digestive system of Bali cattle will provide a clear and precise picture if abnormalities occur in the organs in the digestive system. This study aims to determine the anatomical and morphometric structures of the small intestine and large intestine of Bali cattle. Samples were taken from 14 Bali cattle and based on gross pathology examination declared healthy. The results showed that the average length of the small intestine including the duodenum, jejunum and ileum are 473.07 cm, 529.64 cm, and 363.64 cm; and successive widths are 5.50 cm, 6.00 cm, and 6.11 cm. While the average length of the large intestine which includes the cecum, colon and rectum are 36.78 cm, 371.21, 50.00 cm; while the width are 9.65 cm, 11.47 cm, and 8.85 cm. Jejunum has the longest size in the small intestine, while in the large intestine the longest size is the colon. The right information and data about the digestive system are very important and useful to support further clinical and preclinical research, and the results of this study can be used as a reference in determining the characterization of Bali cattle .